WEB-BASED SCHOOL LIBRARY INFORMATION SYSTEM - Theresa Sidauruk; Sherina Primita Tarigan; Valentina Padang; Simon Agape Tampubolon; Santo Sihotang; Muhammad Ghafan Hafidz (BIOS: Jurnal Informatika dan Sains, 2023)
As we know that the library is a place to maintain and improve the quality of education, because the management of library information systems that are carried out manually has many shortcomings in terms of retrieving borrower and return data, which makes students sometimes not get the books they want to borrow because they don't know information about the library when they come to the library. And also library administrators are overwhelmed in compiling and searching for borrower data while processing book return data, because the focus of the author's focus is to overcome the shortcomings contained in the library's manual information system, and keep up with the times by using technology utilization using a computer technology-based information system or CBIS (Computer Based Information System). The author takes the title "WEB-BASED SCHOOL LIBRARY INFORMATION SYSTEM" with the hope that through this web-based library information system can help students and also provide convenience for library administrators in managing and monitoring information about the library online.